Accounting learning package / Wong Ai Yieng - Wong, Ai Yieng (2001)
The most important concern confounding the education in the world today is the development of computer-assisted teaching materials, especially interactive multimedia programs that run on personal computers. The first signs of computer-delivered electronic system allowed the user to control, combine and manipulate many different types of media, such as text, sound, video, computer graphics and animation. This project is concerned with the development of an interactive multimedia educational package based on the Sijil Pelajaran Malaysia (SPM) Accounting. This project is implemented as a courseware with the CD-ROM as the storage medium. Besides course materials, this educational package also includes accounting system modules that can let students key in the accounting data and directly check their balance sheet correctly or not. For the purpose maintenance in the future, system administration also provide for teacher. This project is developed by the aid of some authoring tools such as Macromedia Director 7.0 and Visual Basic 6.0, as well as some utility tools, for example Adobe Photoshop used to modify images to get better effect.